2016
DOI: 10.2460/javma.249.10.1180
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of spinal epidural empyema in five dogs

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 32 publications
(76 reference statements)
4
58
0
Order By: Relevance
“…Human SEE is a rare medical emergency and accounts for 0•2 to 2/10,000 hospital admissions (Grieve et al 2000). It is even more rarely reported in animals, the majority have been in dogs (Remedios et al 1996, Jerram & Dewey 1998, Cherrone et al 2002, Nykamp et al 2003, Lavely et al 2006, Cross et al 2008, Sutton et al 2010, Monteiro et al 2016 and it has also been reported in two cats (Granger et al 2007, Maeta et al 2010. Clinical signs in dogs and cats are comparable to those in humans, varying from fever, spinal hyperaesthesia to spinal cord dysfunction (Hanigan et al 1990, Rigamonti et al 1999, Grieve et al 2000, Reihsaus et al 2000, Curry Jr et al 2005, Duarte & Vaccaro 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Human SEE is a rare medical emergency and accounts for 0•2 to 2/10,000 hospital admissions (Grieve et al 2000). It is even more rarely reported in animals, the majority have been in dogs (Remedios et al 1996, Jerram & Dewey 1998, Cherrone et al 2002, Nykamp et al 2003, Lavely et al 2006, Cross et al 2008, Sutton et al 2010, Monteiro et al 2016 and it has also been reported in two cats (Granger et al 2007, Maeta et al 2010. Clinical signs in dogs and cats are comparable to those in humans, varying from fever, spinal hyperaesthesia to spinal cord dysfunction (Hanigan et al 1990, Rigamonti et al 1999, Grieve et al 2000, Reihsaus et al 2000, Curry Jr et al 2005, Duarte & Vaccaro 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Successful medical management has been recently described in veterinary medicine suggesting that non-surgical treatment should also be considered (Granger and others 2007, Escriou and others 2011, Song and others 2015, Monteiro and others 2016). …”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge there are only eight previous cases described in the veterinary literature of spinal epidural infections and successful medical management, of which only two were described as abscesses (Remedios and others 1996, Song and others 2015) as opposed to empyemas/infections (Escriou and others 2011, Monteiro and others 2016). In one case the abscess was localised at the level of the lumbosacral junction (Remedios and others 1996) and in the other it extended from the foramen magnum to C2 (Song and others 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations